(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Thearticleis theoretical, and its main purposeisto answer the question: what is entrepreneurshipand what areits types? andwhat is theprocessof entrepreneurshipscene. The articlewas basedondomestic and foreignliteraturedealingentrepreneur-ship.